(untitled) (Research, Society and Development, 2021)
In recent years, agroforestry and silvopastoral systems have been gaining ground in rural areas, especially due to great acceptance by the population of products from locations that preserve the environment, being able to produce food and preserve the natural resources. This study aimed to evaluate the temporal variation of the chemical attributes of the soil in pasture areas managed with silvopastoral system and full sun (monoculture). The areas were evaluated in 2011, 2014 and 2017. Soil samples were collected at depths of 0-10 cm and 10-20 cm. Both systems presented reductions in the levels of organic matter over the evaluated period, reflecting the degradability of the material deposited in the soil. Nevertheless, it is worth mentioning that the silvopastoral system (SPS) was more efficient in maintaining the organic component when compared with monoculture, despite not maintaining regularity in the levels of organic matter in the soil. As for the other chemical parameters, there were also changes, especially related to phosphorus (P) and potassium (K). For P, low replacement via organic material from the pasture and/or native trees in the SSP system were observed, resulting in a marked reduction over time. As for K, the presence of the nutrient was critical in both studied systems and depths, showing low replacement through litter.